Peranan Satuan Polisi Pamong Praja Provinsi Sumatera Utara Dalam Penegakan Peraturan Daerah Nomor 1 Tahun 2021 Di Provinsi Sumatera Utara - Binsar Limbong; Humaizi; Hatta Ridho (Universitas Medan Area, 2023)
The purpose of this study is: to analyze the position, role and obstacles faced by the Civil Service Police Unit in enforcing regional regulation no. 1 of 2021 concerning Enforcement of Discipline and Law Enforcement of Health Protocols in the Prevention and Control of Covid 19 in North Sumatra Province. The method used is descriptive with a qualitative approach. The data were obtained through primary data (results of field interviews with informants) and secondary data (literature, books and laws and regulations). The results of the study concluded that the position of the Civil Service Police Unit in Enforcing Regional Regulation No. 1 of 2021 concerning Enforcement of Discipline and Law Enforcement of Health Protocols in the Prevention and Control of Covid 19 in North Sumatra Province. This position authorizes Satpol PP to carry out outreach regarding the implementation of the health protocol and impose sanctions on violators. Its role is as an extension of the Governor of North Sumatra to carry out the instructions of the Regulations, especially in articles 11-13. Factors that become obstacles include the weak application of sanctions due to human values ​​that emerge in officers and overlapping authorities with other law enforcers and indirectly obscuring the role of Satpol PP as stated in Articles 11-13.